Decoding the Ambiguity of "the Nun's Priest's Tale"1 - Zuraikat, Malek (Dirasat: Human and Social Sciences, 2021)
The multi-layered complexity of "the Nun's Priest's Tale" seems praiseworthy, but it potentially causes readers to feel uncertain of what the tale is all about. Derek Brewer summarizes the various critical readings of the tale and concludes that the presence of such sundry critical viewpoints about the same literary piece induces one to wonder, "what is this nature; what is the status of the text, that can sustain such inconsistencies, give rise to such diverse interpretations? How should we accommodate such variety?" (1984: 91). To resolve such a problem, Brewer suggests that "we have to take Chaucer's own word for it [the tale]: 'my tale is of a cok'" (1984: 106). This viewpoint seems insightful; nevertheless, it explains neither the structural nor thematic ambiguity of the tale. Also, it pays little attention to how centralizing Chauntecleer's dream experience, which constitutes the fulcrum of "the Nun's priest's Tale", into the narrative influences the tale's clarity and confounds its thematic value. Thus, this paper discusses the main events that obscure the structural and thematic texture of "the Nun's Priest's Tale" and explains how the tale's complex structure engenders its own thematic ambiguity and vagueness. The paper analyzes the dominant ambiguity and vagueness of "the Nun's priest's Tale" by examining the role of the narrator as well as the influence of Chauntecleer's conversations with both Pertelote and the Fox in establishing the tale's mysterious scaffold.